To find the length of side \( YZ \) in triangle \( XYZ \) with vertices \( X(-6, 2) \), \( Y(-4, 6) \), and \( Z(-2, 2) \), we can use the distance formula:
\[ d = \sqrt{(x_2 - x_1)^2 + (y_2 - y_1)^2} \]
Let's identify the points:
- \( Y(-4, 6) \)
- \( Z(-2, 2) \)
Now we can calculate the length of \( YZ \):
\[ YZ = \sqrt{((-2) - (-4))^2 + (2 - 6)^2} \]
Calculating the differences:
\[ = \sqrt{(-2 + 4)^2 + (2 - 6)^2} \] \[ = \sqrt{(2)^2 + (-4)^2} \] \[ = \sqrt{4 + 16} \] \[ = \sqrt{20} \] \[ = 2\sqrt{5} \]
Now, approximating \( 2\sqrt{5} \):
First, we know that \( \sqrt{5} \approx 2.236 \), so:
\[ 2\sqrt{5} \approx 2 \times 2.236 \approx 4.472 \]
Rounding to one decimal place:
\[ \text{Length of } YZ \approx 4.5 \]
Thus, side \( YZ \) has a length of approximately 4.5.